Analisis Pengaruh Kepercayaan, Kemudahan, Kualitas Informasi, Produk Halal, Terhadap Minat Pembelian Di Shopee Barokah (Studi Kasus Pada Generasi Z Muslim Di Samarinda) - Nur Maulidiah Alfani; Akhmad Nurzaroni; Muhamad Hasbi (Borneo Islamic Finance and Economics Journal, 2022)
The development of the internet is currently very rapid, and provides benefits and convenience in various daily activities. One of the many internet users in Indonesia is generation Z. Generation Z was born when the use of technology was rife and this generation prefers to make shopping transactions online through e-commerce sites or from social media, because it is considered more practical, economical time, and can be anywhere, and shopping activities are now more practical and easier with the presence of a marketplace that provides a variety of goods needed by consumers, namely the shopee marketplace, because it's an easy way to shop and many people like it. And Shopee has also developed its application by working with Muslim consumers by publishing its newest feature, the Shopee Barokah feature. This study aims to determine the effect of trust, convenience, quality of information, and halal products on purchase intention at shopee barokah (a case study on generation Z Muslims in Samarinda).This study uses quantitative research methods. The population of this study is Generation Z Muslims in Samarinda. The sampling technique uses a probability sampling technique or random sample where each individual or each sampling unit in the population has or has the same opportunity to be taken or selected as a sample with a total of 96 respondents. Data collection techniques used are questionnaires and documentation. The data analysis method used is validity test, reliability test, classical assumption test, multiple regression analysis test, t test, F test, coefficient of determination test using SPSS.The results obtained are the variables of trust and convenience partially have no significant effect on buying interest at shopee barokah. While the variable quality of information and halal products partially has a significant effect on buying interest at shopee barokah. The variables of trust, convenience, quality of information, and halal products simultaneously have a significant effect on buying interest at shopee barokah. The variables of trust, convenience, quality of information, and halal products affect buying interest at shopee barokah by 75.0%.